2014
DOI: 10.1016/j.biomaterials.2014.01.081
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ex vivo expansion of adult mesenchymal stem cells by fetal mesenchymal stem cell ECM

Abstract: Large-scale expansion of highly functional adult human mesenchymal stem cells (aMSCs) remains technologically challenging as aMSCs lose self renewal capacity and multipotency during traditional long-term culture and their quality/quantity declines with donor age and disease. Identification of culture conditions enabling prolonged expansion and rejuvenation would have dramatic impact in regenerative medicine. aMSC-derived decellularized extracellular matrix (ECM) has been shown to provide such microenvironment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
119
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(131 citation statements)
references
References 36 publications
11
119
1
Order By: Relevance
“…Further, BMSCs that were cultured on plastic for 6 passages and then moved to fetal DECM displayed a 2.2-fold higher cell count after 3 additional passages relative to BMSCs cultured on plastic throughout, suggesting that fetal DECM was able to rescue the aged phenotype of adult BMSCs. 47 Taken together, these studies show that DECM formed by young cells is able to independently enhance the proliferation of older cells. As mentioned above, this finding suggests a possible utility of fetal DECM in generating sufficiently large MSC populations derived from elderly donors for use in regenerative therapies.…”
Section: Rejuvenation Of Elderly Cells By Young Ecmmentioning
confidence: 75%
See 1 more Smart Citation
“…Further, BMSCs that were cultured on plastic for 6 passages and then moved to fetal DECM displayed a 2.2-fold higher cell count after 3 additional passages relative to BMSCs cultured on plastic throughout, suggesting that fetal DECM was able to rescue the aged phenotype of adult BMSCs. 47 Taken together, these studies show that DECM formed by young cells is able to independently enhance the proliferation of older cells. As mentioned above, this finding suggests a possible utility of fetal DECM in generating sufficiently large MSC populations derived from elderly donors for use in regenerative therapies.…”
Section: Rejuvenation Of Elderly Cells By Young Ecmmentioning
confidence: 75%
“…21 Ng et al, however, found that the amount of ECM produced per cell by human fetal BMSCs and adult BMSCs was 1.4 § 0.6 and 0.5 § 0.2 mg, respectively, indicating that ECM production by fetal BMSCs is significantly greater than that by adult BMSCs. 47 BMSCs from elderly (1 y old) SD rats exhibited a diminished ability to generate a chondrogenic matrix in vitro relative to immature (1 week old) and young adult (12 weeks old) rats. 97 Interestingly, Erickson and colleagues reported that bovine fetal BMSCs produced 2-15 times more GAG (in response to TGFb3) and collagen than adult or juvenile BMSCs, 58 and it was noted by our laboratory that human adult SDSC expansion on fetal DECM yielded a greater GAG content per pellet, as well as a higher GAG/DNA ratio, than did expansion on adult DECM or plastic.…”
Section: Msc Specific Changes In Ecm Compositionmentioning
confidence: 99%
“…The process of preparing decellularized ECM allows cells to be removed from a cellular sheet formed in culture, leaving only ECM components behind. Ng et al have shown that fetal MSC-derived ECM enhances the proliferation and differentiation potential of adult MSCs with the use of decellularized ECM [29]. He and his coworkers have also found that ECM deposited by bone marrow MSCs (BM-MSCs) promotes cell proliferation but reduces levels of intracellular reactive oxygen species.…”
Section: Introductionmentioning
confidence: 95%
“…[14][15][16][17] Important in vitro and in vivo studies have elucidated some of the mechanisms by which bone marrow ECM dictates the fate of MSCs. [18][19][20][21][22] For example, bone marrow stromal cells harvested from knockout mice lacking the ECM component biglycan exhibited defects in the ability to differentiate into osteoblasts. 23 In two other studies, MSCs that were cultured on ECM made by bone marrow cells exhibited enhanced proliferation and restrained osteogenic differentiation while preserving their multidifferentiation capacity.…”
Section: Introductionmentioning
confidence: 99%